MENTAL HEALTH ISSUES: REASONS AND STRATEGIES FOR ACTION FROM THE LENS OF YOUNGSTERS IN SINDH (The Research of Medical Science Review, 2025)
Mental health illnesses start in late childhood or early adolescence and worsen as someone becomes older. An important independent contributor to the global disease burden is mental diseases. Neuropsychiatric illnesses lead to the world's disease burden, depression, and other prevalent mental disorders that can be permanently incapacitating. These projections highlight the significance of mental illnesses for general health. The research aims to explore the reasons for mental stress in youngsters in Sindh and to analyze the effectiveness of the strategies they use to cope with their mental stress. The qualitative phenomenological study design was used with a sample size of 30 youngsters aged between 16 -25 years from varied socioeconomic and cultural backgrounds to extract in-depth data through semi-structured interviews and focused group discussions. The ethical guidelines are followed as per the BERA framework. The participants signed the written consent letters and their true identity is kept secret as per the BERA framework. The theoretical framework that underpins this research is Cox's theory of stress (1985). The data was analyzed through thematic analysis. The themes were created after a careful coding and chunking process. The two basic emerging factors that are responsible for mental stress are family-related factors and social factors. The major themes that erupted from data regarding coping mechanisms are socioemotional support, lifestyle factors, and professional support. The major findings of the research reveal that family issues and financial crises lead to mental stress in youngsters and the coping strategies utilized by them are family support and meditation. Some of the participants were in Favor of seeking mental health professional guidance. The recommendations are proposed based on the findings suggest that there should be more mental health professionals with cheaper fee charges so the general public can access them conveniently. Research can benefit youngsters, parents, guardians, educators, Mental health professionals, and policymakers.